Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Pada Toko Pakaian Suplier ID Di Kabupaten Badung - Dewa Putu Sastra Wiguna; Ni Made Hartini (Universitas Triatma Mulya, 2025)
Purchasing decisions really determine the success of a company or business. Increasing the success of purchasing decisions by implementing a marketing mix including product quality, price and promotions carried out in a business. This research examines the influence of several factors and identifies the most important factors when making judgments about what to buy from Supplier ID clothing retailers in Tabanan Regency: product quality, price, and promotions. The sample consisted of 95 respondents and the research methodology used was quantitative. Purposive sampling, a non-probability sampling approach, was used in the sampling process. Validity and reliability tests, traditional assumption tests, multiple linear regression analysis, T tests, and beta coefficients are examples of analytical approaches. The results of the regression model are displayed in the research analysis as Y = 0.782 + 0.287 X1 + 0.232 X2 + 0.230 X3. It was found that judgments about what to buy were positively influenced by product quality. Pricing significantly influences the assessment of what to buy. Purchasing decisions are greatly influenced by promotions. The standardized beta coefficient value of the product quality variable is 0.419, while the beta values ​​of price and promotion are 0.220 and 0.252 respectively, indicating that the product quality variable has a significant effect on purchasing choices.